2001
DOI: 10.1093/jurban/78.4.571
|View full text |Cite
|
Sign up to set email alerts
|

Female-Initiated Barrier Methods for the Prevention of STI/HIV: Where Are We Now? Where Should We Go?

Abstract: The female condom has been on the US market for over 8 years and was hailed as a method that would allow women greater control in protecting themselves

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 45 publications
1
27
0
1
Order By: Relevance
“…In particular, innovative and multiple prevention options, including some that women can control, are needed immediately. Vaginal microbicides, currently in development (Hardy, de Padua, Jimenez, & Zaneveld, 1998;Harrison, Rosenberg, & Bowcut, 2003;McCormack, 2002;Stone, 2002), and female condoms (Feldblum, 2001;Gollub, 2000;Hoffman, Mantell, Exner, & Stein, 2004;Latka, 2001) are important prevention methods that might be central to stemming the pending flood of new infections through risky sex. Greater knowledge of the acceptability and feasibility of using these methods for high-risk women is a priority for AIDS prevention research, particularly in China's shifting social context.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, innovative and multiple prevention options, including some that women can control, are needed immediately. Vaginal microbicides, currently in development (Hardy, de Padua, Jimenez, & Zaneveld, 1998;Harrison, Rosenberg, & Bowcut, 2003;McCormack, 2002;Stone, 2002), and female condoms (Feldblum, 2001;Gollub, 2000;Hoffman, Mantell, Exner, & Stein, 2004;Latka, 2001) are important prevention methods that might be central to stemming the pending flood of new infections through risky sex. Greater knowledge of the acceptability and feasibility of using these methods for high-risk women is a priority for AIDS prevention research, particularly in China's shifting social context.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, intravaginal practices, such as vaginal douching, have relevance in topical microbicide acceptability, and clinical trials of candidate topical microbicide. 34,[38][39][40] Topical microbicide is an STI transmission prevention technology that is being explored internationally with increasing interest. [41][42][43] New laboratory technologies may facilitate research on the influence of douching behavior on vaginal milieu, such as microflora 44 and proinflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…These issues are not unique to the female condom; in fact, very similar resistance was observed with the introduction of the tampon for sanitary protection in the 1930s. 2 With correct and consistent use, the female condom is as effective as other barrier methods and has no known adverse effects or risks to health. 3 A wide range of acceptability studies and field projects in many different countries and social and economic settings have shown that the female condom is acceptable to a number of women and men.…”
mentioning
confidence: 99%